Jeremiah a study in ancient Hebrew rhetoric - Lundbom, Jack R. (Winona Lake, IN Eisenbrauns, 1997)
Includes bibliographical references and indexes
Originally presented as the author's thesis -- Graduate Theological Union, Berkeley, 1973.
Keywords: Bible. O.T. Jeremiah -- criticism, interpretation, etc; Bible. O.T. Jeremiah -- language, style